1984
DOI: 10.1021/jm00367a019
|View full text |Cite
|
Sign up to set email alerts
|

2-Acetylpyridine thiosemicarbazones. 9. Derivatives of 2-acetylpyridine 1-oxide as potential antimalarial agents

Abstract: In view of the antimalarial activity in mice of 2-acetylpyridine thiosemicarbazones, a series of analogous 1-oxides was prepared for evaluation. Their synthesis was achieved by the reaction of 2-acetylpyridine 1-oxide with methyl hydrazinecarbodithioate to give methyl 3-[1-(2-pyridinyl 1-oxide)ethylidene]hydrazinecarbodithioate (II). Reaction of the latter intermediate with secondary amines afforded the desired 2-acetylpyridine 1-oxide thiosemicarbazones (III). Reduction of the azomethine linkage of II with Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(32 citation statements)
references
References 6 publications
0
28
0
4
Order By: Relevance
“…In some instances the 1-oxides were virtually devoid of antibacterial properties when the parents were active. An impor tant corollary, however, is that the 1-ox ides are less toxic than the parent com pounds [11] which would make the former possibly more attractive as antibacterial agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances the 1-oxides were virtually devoid of antibacterial properties when the parents were active. An impor tant corollary, however, is that the 1-ox ides are less toxic than the parent com pounds [11] which would make the former possibly more attractive as antibacterial agents.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and physical properties of 2-acetylpyridine-1 -oxide thiosemicarbazones and thiosemicarbazides used in this study have been reported by Scovill et al [11]. The compounds were prepared by the Or ganic Synthesis Section, Division of Experimental Therapeutics, Walter Reed Army Institute of Re search.…”
Section: Test Compoundsmentioning
confidence: 99%
“…All reactions were carried out under nitrogen in flame-dried glassware. 3 , the mixture was refluxed on a water bath for 4-6 h at 60 ℃. The precipitates formed were collected by filtration, washed with hot water and diethyl ether, and finally dried in a vacuum desiccator over silica gel (0.89 g, yield 74%).…”
Section: Reagentsmentioning
confidence: 99%
“…1,2 Derivatives of thiosemicarbazones and their metal complexes were found to be active against influenza, protozoa, smallpox [3][4][5] and to have anticarcinogenic, antibacterial, and antifungal properties. [5][6][7][8] Recent studies revealed that a number of thiosemicarbazones possessed anticonvulsant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The pharma co log i cal ac tiv ity of these com pounds has of ten been related to their che lat ing abil ity with metal ions 3 .…”
Section: Introductionmentioning
confidence: 99%